The effects of menthol on exercise performance and thermal sensation: A meta-analysis - Jeffries, O.; Waldron, M. (Journal of Science and Medicine in Sport, 2019)
Objectives: Menthol is an organic compound with non-thermal cooling properties that has been shown to relieve thermal strain associated with exercise in the heat; however, its effects on performance have not been systematically analysed. The aims were to determine the effects of menthol applied (1) internally and (2) externally on exercise performance and thermal sensation. Design: Meta-analysis Methods: A search was performed using various databases in August 2018. The studies were screened using search criteria for eligibility. Thirteen peer-reviewed articles were identified for inclusion in a primary analysis on the effect of menthol on exercise performance; subsequently eleven of these articles were included in a secondary analysis on the effect of menthol on thermal sensation during exercise. A sub-analysis examining the application method was also performed. Results: Menthol improved overall exercise performance (Hedges` g = 0.33, 95% CI -0.00, 0.65 P = 0.05), demonstrating greater effects when applied internally (Hedges` g = 0.40, 95% CI 0.04, 0.76, P = 0.03). Thermal sensation was also lowered overall across all studies (Hedges` g = -0.54, 95% CI -0.67, -0.42, P < 0.001). Conclusions: Exercise performance can be improved by application of non-thermally cooling menthol, which also reduces perceptual measures of thermal sensation. Internal application appears to be the best strategy to improve performance.